2003
DOI: 10.1021/bm034065g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Exchange on the Solid Structure and Dissolution Behavior of Cellulose

Abstract: Effects of solvent exchange and milling on the solid structure of cellulose were investigated, using small- and wide-angle X-ray scattering and solid-state NMR. The solvent exchange facilitated the dissolution of cellulose in LiCl/DMAc with no change of the crystalline structure of cellulose. In contrast, the milling never facilitated the dissolution of cellulose, though the crystalline structure was almost destroyed. These facts show that the crystalline structure of cellulose hardly affects the dissolution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…In fact, several reports in the literature noted that depending on the acid hydrolysis process used, variability in shapes and sizes are not consistent from extraction to extraction and can induce agglomeration of smaller cellulose fibers into larger fibers with various geometries [29][30][31]. Hence the stages of drying of cellulose are threefold-(1) a constant ratedrying period, (2) the first falling rate-drying period, and (3) the second falling rate-drying period [32][33][34][35]. In stage 1, water begins to evaporate, causing cellulose particles to 8 International Journal of Chemical Engineering begin diffusing closer together and eventually exposing the polymer's surface enabling surface water evaporation (the first falling rate-drying period).…”
Section: (D)mentioning
confidence: 99%
“…In fact, several reports in the literature noted that depending on the acid hydrolysis process used, variability in shapes and sizes are not consistent from extraction to extraction and can induce agglomeration of smaller cellulose fibers into larger fibers with various geometries [29][30][31]. Hence the stages of drying of cellulose are threefold-(1) a constant ratedrying period, (2) the first falling rate-drying period, and (3) the second falling rate-drying period [32][33][34][35]. In stage 1, water begins to evaporate, causing cellulose particles to 8 International Journal of Chemical Engineering begin diffusing closer together and eventually exposing the polymer's surface enabling surface water evaporation (the first falling rate-drying period).…”
Section: (D)mentioning
confidence: 99%
“…The increase in the surface roughness of cellulose has been already shown by the increase in the fractal dimension, although it was investigated in the dried state. 6 Considering these results, it is concluded that the increase in the amount of small pores induced by the DMAc treatment leads to the enlargement of the surface area and consequently facilitates the access of solvent molecules to the cellulose solid, resulting in the facilitated dissolution in LiCl/DMAc.…”
Section: Saxs Measurementsmentioning
confidence: 93%
“…We have formerly shown that the structural heterogeneity of cellulose in the dried state as observed by SAXS is evaluated by fractal dimension. 6 Because the fractal nature originates in the aggregation of cellulose microfibril, it is considered that the value of R g reflects the size of cellulose microfibril as an elemental structural unit of cellulose.…”
Section: Saxs Measurementsmentioning
confidence: 99%
See 2 more Smart Citations